THE IMPACT OF HYPERGLYCAEMIA ON MORBIDITY AND MORTALITY OF ACUTE CORONARY SYNDROMES AND ACUTE MYOCARDIAL INFARCTION - Sahibzada, Palwasha; Khan, Ambreen Ali; Sahibzada, Waheed A (Journal of Ayub Medical College Abbottabad, 2009)
Background: Though diabetes and hyperglycaemia are well known risk factors for morbidity and mortality associated with Coronary Heart Disease, there are no studies published from Pakistan on the impact of non-diabetic hyperglycaemia on these indices. The present study was undertaken to fill the gap in knowledge related to this aspect of hyperglycaemia in Pakistani patients. Methods: We studied 166 patients admitted to our coronary care unit from May 2008 to March 2009 with acute coronary syndrome and acute myocardial infarction. The patients were divided into three groups (a) Diabetic group (b) Impaired glucose group and (c) Normal glucose group according to the American Diabetic Association criteria. Results: It was observed that with increasing level of hyperglycaemia there was an increase in the mortality, with a p-value of 0.058. Hyperglycaemia was also associated with impaired left ventricular function and clinical evidence of left ventricular failure. Insulin therapy was under utilized and may have contributed to increased morbidity and mortality. Keywords: Coronary artery syndromes, Myocardial infarction, Diabetes mellitus, Hyperglycaemia